1992
DOI: 10.1177/153331759200700302
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dementia: The confusion of numbers

Abstract: The prevalence of dementia in American society is an important statistic. In order to allocate public dollars to both research and service programs designed for cognitively impaired persons and their families, and to aid policy makers at the community level in planning for services and facilities to meet the needs of their populations, accurate estimates of persons with dementia are critical. Inaccurate figures can lead to inefficiency in allocating resources at both the national and local levels, underutiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Yet, in relation to communication about health and risk, Jones (2013: 40-41) raises a more fundamental concern about the use of numbers, in particular where it is not clear what has been counted, and how. In their review of the dementia prevalence literature, Blume, Persily and Mintzer (1992) reported the tendency for dementia statistics to be calculated in inconsistent ways, including whether or not different types of dementia were taken into account. These and other complexities surrounding the calculation of prevalence information about dementia are, however, not mentioned in the articles, but are conveniently obscured, we suggest, so as not to undermine the shock value and fear factor that the media narratives undoubtedly intend to produce.…”
Section: Representing Dementia: Battles and Racesmentioning
confidence: 99%
“…Yet, in relation to communication about health and risk, Jones (2013: 40-41) raises a more fundamental concern about the use of numbers, in particular where it is not clear what has been counted, and how. In their review of the dementia prevalence literature, Blume, Persily and Mintzer (1992) reported the tendency for dementia statistics to be calculated in inconsistent ways, including whether or not different types of dementia were taken into account. These and other complexities surrounding the calculation of prevalence information about dementia are, however, not mentioned in the articles, but are conveniently obscured, we suggest, so as not to undermine the shock value and fear factor that the media narratives undoubtedly intend to produce.…”
Section: Representing Dementia: Battles and Racesmentioning
confidence: 99%
“… 100 These additional manifestations are often major risk factors for caregiver distress and nursing home placement. 101 An alternative approach to the treatment of individuals with dementia who have severely agitated behavior is the use of behavioral environmental techniques, implemented in conjunction with, or in place of, traditional pharmacological treatments. 102 …”
Section: Nonpharmacological Interventionsmentioning
confidence: 99%
“…Approximately 10% of persons who reach the age of 65 will develop Alzheimer's disease (AD) or another type of dementia. 1 AD and other dementias usually present with two syndromes, a cognitive syndrome and a behavioral syndrome, 2 which overlap (in most patients) during the course of the disease. 3 The cognitive syndrome is characterized by deficits in memory, language, visual constructional abilities, and other areas of intellectual functioning.…”
mentioning
confidence: 99%